Novel Carbon-Based Magnetic Luminescent Nanocomposites for Multimodal Imaging - Liu, Fangfang; Mou, Xiaoming; Song, Jimei; Li, Qin; Liu, Jinliang (Frontiers in Chemistry, 2020)
Multifunctional nanocomposites can combine multiple functions into a single nanosystem and thus have attracted extensive interest in various fields. The combination of magnetic and upconversion luminescent nanoparticles into one single nanoplatform, which have a good application in biomedical fields such as bio-magnetic separation, magnetic resonance imaging (MRI), and optical imaging, is highly desirable. Here we reported multifunctional nanocomposites by using hollow carbon sphere to integrate magnetic Fe3O4 and upconversion nanoparticles (UCNPs) into one nanosystem. The as-prepared UCNPs/Fe3O4@h-C have near-infrared (NIR) luminescence under 980 nm excitation and superparamagnetism. In addition, since the carbon layer can absorb NIR light and transfer it into heat with high efficiency, the nanocomposites can realize photo thermal (PT), upconversion luminescence (UCL) and MRI tri-mode imaging. The UCNPs/Fe3O4@h-C might be further utilized as a potential theranostic agent, including its in-depth monitoring through luminescent imaging and MRI diagnosis, as well as its direct use in tumors as a photothermal therapy (PTT) agent.